Comparative diagnostic accuracy of RIPASA and Alvarado scores for acute appendicitis - Waleed Ahmad; Fajar Saqib; Binish Tahreem; Mohammed Hammad Jaber Amin (Medicine, 2026)
To compare the diagnostic accuracy of the Raja Isteri Pengiran Anak Saleha Appendicitis (RIPASA) and Alvarado scoring systems in patients with suspected acute appendicitis using histopathology as the gold standard. A prospective study was conducted from December 2024 to April 2025 involving 100 patients at Ghurki Trust Teaching Hospital, Lahore. Patients presenting with right iliac fossa pain were assessed using both scoring systems. A score of 7 or higher from the Alvarado scale and 7.5 or higher from RIPASA indicated a positive result. Histopathological examination functioned as the definitive diagnostic method to establish correct diagnoses. The calculation of diagnostic accuracy and predictive values, together with sensitivity and specificity, was performed for both systems. In 100 patients (66% men and 64% under 40 years), histopathology showed appendicitis in 90% of patients. The RIPASA score demonstrated higher sensitivity (90.00%, 95% confidence interval [CI]: 81.85–95.31) compared to the Alvarado score (76.67%, 95% CI: 66.64–84.94), whereas Alvarado showed higher specificity (70.00%, 95% CI: 34.75–93.33) than RIPASA (20.00%, 95% CI: 2.52–55.61). Both scores had high positive predictive values (RIPASA: 91.01%; Alvarado: 95.83%) and low negative predictive values (RIPASA: 18.18%; Alvarado: 25.00%). Overall diagnostic accuracy was 83.00% for RIPASA and 76.00% for Alvarado. The RIPASA scoring system was found to be more sensitive and overall more diagnostic than the Alvarado score, but this difference was not found to be statistically significant. Both scoring systems are still clinically useful, and low scores cannot be used alone to rule out acute appendicitis.